The Diagnostic value of lung-to-liver signal intensity ratio as an indicator of fetal lung maturity in third-trimester pregnancy using magnetic resonance imaging. - AlHaidery, Fatimah; Abd Kadhim, Dr Mohammed (Karbala Journal of Medicine, 2022)
Background: fetal MRI is an effective and non-invasive more accurate method for examining fetal lung development and predicting fetal respiratory outcomes. Aims of the study: to study fetal lung-to-liver signal intensity ratio (LLSIR) using MR imaging T2-weighted images as an indication of fetal lung maturity and prediction of neonatal respiratory outcome in third-trimester pregnancy and to establish an optimal cut-off value of LLSIR. Patients and Methods: a prospective study was conducted on 40 fetuses from 39 pregnant women who delivered within 24 hours of MRI scan during the period from January 2021 and January 2022 in AL-Imamain Al-Kadhimain Medical city/ Baghdad/ Iraq. LLSIR was evaluated using Half-Fourier acquisition single-shot turbo spin-echo (HASTE) MRI. Using receiver operating characteristic (ROC) curve analysis, the optimal cut-off value for the LLSIR to predict respiratory prognosis after delivery was determined. Results: the gestational ages ranged from 28.1-to 40 weeks (mean, 34.8weeks). A significant relationship between magnetic resonance LLSIR and gestational age was demonstrated (p-value 0.001). The non-respiratory distress syndrome group had higher LLSIR compared with the respiratory distress syndrome group (2.81±0.32vs. 2.19±0.18, p-value 0.001). The term group had higher LLSIR compared with the preterm group (2.87±0.34 vs 2.34±0.29, p-value 0.001). ROC curve analysis showed LLSIR at a cut-off value of LLSIR ≤ 2.32 and AUC=0.977, revealing high sensitivity (100%) and high specificity (88.9%). Conclusions: a significant relationship between fetal lung maturation and the LLSIR during the third trimester, as measured by T2-weighed MRI, and can be used as a prognostic indicator for the neonatal respiratory outcome. The best cut-off value that predicts the neonatal respiratory outcome is ≤ 2.32 Keywords: fetal lung maturity, gestational age, third trimester, Lung-to-liver signal intensity ratio · Magnetic resonance imaging